2022
DOI: 10.3389/fendo.2022.829658
|View full text |Cite
|
Sign up to set email alerts
|

Association of Human Whole Blood NAD+ Contents With Aging

Abstract: BackgroundNAD+, nicotinamide adenine dinucleotide, is mostly described to associate with the aging process. We aimed to investigate the association between human whole blood NAD+ contents and aging in a relative large-scale community-based population and further to address the gender impact on this association.MethodsWe recruited 1,518 participants aged over 18 years old and free of cardiovascular and any type of cancer from the Jidong community from 2019 to 2020. Whole blood NAD+ level was measured by cycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
2
15
1
Order By: Relevance
“…It is difficult to determine how the NAD + concentrations used in this study relate to the actual extracellular concentration of NAD + in vivo. In human blood, NAD + concentrations were determined to be approximately 33 µM (Yang et al, 2022). While this is below the threshold for a significant growth inhibition of Spn in our study, concentrations might be higher in the infection-relevant microenvironments like the lung alveoli, especially upon infection-induced host cell lysis (Adriouch et al, 2007).…”
contrasting
confidence: 51%
“…It is difficult to determine how the NAD + concentrations used in this study relate to the actual extracellular concentration of NAD + in vivo. In human blood, NAD + concentrations were determined to be approximately 33 µM (Yang et al, 2022). While this is below the threshold for a significant growth inhibition of Spn in our study, concentrations might be higher in the infection-relevant microenvironments like the lung alveoli, especially upon infection-induced host cell lysis (Adriouch et al, 2007).…”
contrasting
confidence: 51%
“…The authors speculate there may be less cellular NAD + release via connexin 43 hemichannels and/ or increased NAD + consumption via enzymes such as CD38 in men. In contrast, Yang et al (2022) report higher circulating NAD + levels in men than women in a study of 1,518 participants from the Jidong community, 18 years of age and over (245). Breton et al (246), found no sex differences in blood NAD + levels in a smaller French study, although there was a trend to an age-dependent decline in NAD + in males and not females.…”
Section: Sex Effectsmentioning
confidence: 94%
“…More precisely, the knockout animals experienced a decreased ratio of oxidized (NAD + ) to reduced (NADH) nicotinamide adenine dinucleotide in the damaged tissue [ 24 ]. Many studies have confirmed the relevance of NAD + in energy metabolism and electron transfer reactions [ 24 , 102 , 103 , 105 , 106 ], whereas its elevated levels of NAD + may upgrade SIRT1 activity [ 24 , 102 , 103 , 105 ]. It deserves mentioning that NAD + possess essential function in the positive regulation of SIRT1 [ 102 , 103 , 105 ].…”
Section: Renalase's Antioxidative Anti-inflammatory and Antiapoptotic...mentioning
confidence: 99%